Sur Racine de Barthes : le Degré zéro de l’objet critique ? - Marta Teixeira Anacleto (Carnets)
The starting point for this paper is Roland Barthes’ polemical foreword to his Sur Racine (published in April 1963), in which Barthes views Racine as the « degree zero of the critical object » – an expression which should be placed in the context of his many interrogations regarding the « classical » authors of the 19th century. I will attempt to show how this postulate is transformed into a significant epistemic interrogation at the core of the Barthesian theory of language and literature. To achieve this, I will look into the reasons for Barthes’ decision to convey the Racinian language and its tragic universe through a « deliberately closed analysis » of the dramatist’s plays and the reconstitution of a Racinian anthropology, « both structural and analytical », as well as psychoanalitycal. This reflection will be based on the theoretical and critical dialogue which can nowadays be construed between Sur Racine, the modern tragic sense of Berenice, and the contemporary production of this play staged by the Portuguese director Carlos Pimenta (2005).